Developing doctoral students' / researchers' understanding of the journal peer-review process. Issue 2 (July 2021) - Hanafizadeh, Payam; Shaikh, Aijaz A.
Abstract: A growing body of knowledge has confirmed that the journal peer-review process is an integral part of the scientific publication process and provides demonstrable benefits to journal editors and authors. This study aims to develop doctoral students' understanding of the journal peer-review process and highlight the most common errors and pitfalls reviewers identify in novice authors' manuscripts, which could lead to rejection. A qualitative content analysis research method was used to analyse the primary data as experience collected from senior researchers, editors and associate editors. Among the major contributions of this study is an interactive diagram that provides an overview of the journal peer-review process and identifies the common pitfalls in manuscripts, as well as a comprehensive manuscript submission checklist. Highlights: We aim to develop doctoral students'/researchers' understanding of the journal peer-review process. We highlight common errors & pitfalls reviewers identify in novice authors' manuscripts, leading to rejection. We provide an interactive diagram that comprehensively depicts the journal peer-review process. We also provide a comprehensive manuscript submission checklist.